Planning ability in Schizophrenia - Holt, Daniel (2012)
This publication-based thesis investigates planning ability in psychiatric patients with schizophrenia, combining a problem solving perspective with a psychometric approach to assessing executive functions. The manuscripts presented address four research questions: (1) Is the newly developed Plan-a-Day test a reliable and valid measure of planning ability in schizophrenia? (2) Is planning ability – in particular as measured by the Plan-a-Day test – predictive of functional outcome? (3) Is a planning and problem solving training based on the Plan-a-Day concept effective in cognitive remediation? (4) How specific is a planning deficit in schizophrenia?